Creación y uso de neologismos en el español jurídico de la Argentina - Chiesa, Ricardo (2009)
This essay, written by the author himself based on a lecture he\ngave, analyzes the status of neologisms in the legal Spanish of Argentina from\na perspective that is interesting both for Law and translation professionals\nand students